Introducing a new tool for greenhouse gas calculation tailored for cropland: rationale, operational framework and potential application - Wassmann, Reiner; Pasco R; Zerrudo J; Ngo DM; Vo TBT; Sander, Björn Ole (Informa UK Limited, 2019)
The new GHG calculator named SECTOR (Source-selective and Emission-adjusted GHG CalculaTOR for Cropland) is based on the IPCC Tier 2 approach for rice as well as other crops. The new features of SECTOR facilitate high flexibility in terms of entering newly obtained emission factors, easy data transfer from crop statistics for entering activity data and detailed specifications of GHG scenarios. A new procedure of entering frequency-based data on current water management practices was also developed. Moreover, the tool allows deviating from the 2006 IPCC Guidelines by considering field records with high background levels of N2O emissions in the overall assessment of GHG emissions.